Representation of Women in South Taleshi Proverbs, Idioms and Expressions (Siyahmazgi Variety) - Safoura Soqrat; Mansour Shabani (مطالعات زبانی و بلاغی)
Proverbs are among the valuable components of folklore and oral literature of any culture, revealing plenty of cultural and historical facts. In the present study, we intend to deal with the representation of women in South Taleshi (Siyahmazgi variety) proverbs, idioms and expressions. The design of this descriptive-analytical research is a mixed methods study with field data collection through semi-structured interview with native speakers.  The collected proverbs, idioms and expressions were determined in terms of meaning, concept and theme and classified in 19 semantic categories. These data were analysed in the framework of Lazar (2007) feminist critical discouse analysis. One of the important results is that, according to the significance level of One-sample Colmogorov-Smirnov Test, there is a significant difference between the types of women representations. The results show that, in the society in question, gender is perceived as an ideological structure; based on hierarchical relations of domination and subordination, women are in the subordinated class and are considered of little value. They are also portrayed as dominated, weak, evil, and greedy.